Effectiveness of primary angioplasty in the treatment of acute myocardial infarction. Analysis of in-hospital and late outcomes in 135 consecutive cases - Leite,Rogério Sarmento (2001)
OBJECTIVE: Evaluate early and late evolution of patients submitted to primary coronary angioplasty for acute myocardial infarction. METHODS: A prospective study of 135 patients with acute myocardial infarction submitted to primary transcutaneous coronary angioplasty (PTCA). Success was defined as TIMI 3 flow and residual lesion <50%. We performed statistical analyses by univariated, multivariated methods and survival analyze by Kaplan-Meier. RESULTS: PTCA success rate was 78% and early mortality 18,5%. Killip classes III and IV was associated to higher mortality, odds ratio 22.9 (95% CI: 5,7 to 91,8) and inversely related to age <75 years (OR = 0,93; 95% CI: 0.88 to 0.98). If we had chosen success flow as TIMI 2 and had excluded patients in Killip III/IV classes, success rate would be 86% and mortality 8%. The survival probability at the end or study, follow-up time 142 ± 114 days, was 80% and event free survival 35%. Greater survival was associated to stenting (OR = 0.09; 0.01 to 0.75) and univessel disease (OR = 0.21; 0.07 to 0.61). CONCLUSION: The success rate was lower and mortality was higher than randomized trials, however similar to that of non randomized studies. This demonstrated the efficacy of primary PTCA in our local conditions.